A mass spectrometry based predictive strategy reveals ADAP1 is phosphorylated at tyrosine 364. (21st June 2018) - Reisdorph, Richard; Littrell‐Miller, BobbiJo; Powell, Roger; Reisdorph, Nichole
Abstract : Rationale: The goal of this work was to identify phosphorylation sites within the amino acid sequence of human ADAP1. Using traditional mass spectrometry based techniques we were unable to produce interpretable spectra demonstrating modification by phosphorylation. This prompted us to employ a strategy in which phosphorylated peptides were first predicted using peptide mapping followed by targeted MS/MS acquisition. Methods: ADAP1 was immunoprecipitated from extracts of HEK293 cells stably transfected with ADAP1 cDNA. Immunoprecipitated ADAP1 was digested with proteolytic enzymes and analyzed by LC/MS in MS 1 mode by high‐resolution quadrupole time‐of‐flight mass spectrometry (QTOF‐MS). Peptide molecular features were extracted using an untargeted data‐mining algorithm. Extracted peptide neutral masses were matched against the ADAP1 amino acid sequence with phosphorylation included as a predicted modification. Peptides with predicted phosphorylation sites were analyzed by targeted LC/MS 2 . Acquired MS 2 spectra were then analyzed using database search engines to confirm phosphorylation. Spectra of phosphorylated peptides were validated by manual interpretation. Further confirmation was performed by manipulating phospho‐peptide abundance using calf intestinal phosphatase (CIP) and the phorbol ester, phorbol 12‐myristate 13‐acetate (PMA). Results: Of five predicted phosphopeptides, one, comprised of the sequence AVDRPMLPQEYAVEAHFK, was confirmed to be phosphorylated on a tyrosine at position 364. Pre‐treatment of cells with PMA prior to immunoprecipitation increased the ratio of phosphorylated to unphosphorylated peptide as determined by area counts of extracted ion chromatograms (EIC). Addition of CIP to immunoprecipitation reactions eliminated the phosphorylated form. Conclusions: A novel phosphorylation site was identified at tyrosine 364. Phosphorylation at this site is increased by treatment with PMA. PMA promotes membrane translocation and activation of protein kinase C (PKC), indicating that tyrosine 364 is phosphorylated by a PKC‐dependent mechanism.